Analisis strategi guru PPKn dalam menanamkan nilai karakter integritas siswa kelas VIII SMP negeri 11 Muaro Jambi - Ananda, Dita Rizki; Anderson, Irzal (Civic Education Perspective Journal, 2024)
The problem of low integrity character values ​​is addressed by the findings of initial observations conducted by researchers at SMP Negeri 11 Muaro Jambi, the article requires a good teacher strategy and is carried out continuously in order to instill integrity character values ​​in students who can shape students to act with integrity within themselves . But in reality the teacher's strategy has been instilled but has not been carried out properly and correctly, it was found that the teacher's strategy in instilling the integrity character values ​​of SMP Negeri 11 Muaro Jambi students was carried out by the teacher through strategy 1). Habituation, there are still students who do not follow habituation 2). Exemplary, teachers still give bad examples to students 3). Providing continuous understanding sentences but in reality understanding is only occasionally given and not continuously, 4) giving punishment in fact the teacher sometimes gives punishment sometimes not 5). Integration into subjects or lesson plans. This study uses a qualitative descriptive methodology. Teachers, students and also student representatives became informants in this study. data collection is done through observation, interviews and documentation. The methods used for data analysis include data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the teacher's strategy in instilling the character value of integrity has not been implemented properly and correctly. This can be seen from the results of field research.